Implementation of halal logistics services from the perspective of logistics service providers in Malaysia : issues and challenges / Azlina Muhammad - Muhammad, Azlina (Research Management Institute, 2014)
Halal logistics is basically the process of managing the procurement, movement , storage, and handling of materials, part of livestock and (semi) finished inventory both food and non-food (and related Information, and documentation flows) through the Organization and the supply chain in compliance with the general principles of shariah law. Malaysia as a modern, progressive and politically stable muslim country, has the opportunity to establish itself as a regional and global hub for halal productions, logistics and trade. So the development regarding the halal logistics, halal product and halal parks have become the national priority. This section will give brief description about the study entitled " issues and challenges in implementing halal logistics". This research is conducted in order to ensure the issues and challenges in implementing halal logistics. This research is conducted in order to find any issues and challenges in implementing halal logistics. As the market demand for halal products and Services has significantly increased, manufacturers and also Operators need to provide more of halal products and also Services. Halal market is growing fast and has increase at an estimated of 25% per year according to the Dewan ekonomi 2011. Halal product is becoming a lucrative business among muslim and also non-muslim countries. The demand for halal products and Services are very high especially at where the largest populations of muslims are located. There are studies being conducted in the area of food.